Cerita rakyat Indramayu sebagai media pendidikan karakter - Alfien, Moh. Fajrul; Andayani, Andayani; Sumarwati, Sumarwati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The urgency of moral education is one of the issues that has recently been discussed. Folklore, which contains noble values, is one of the media that can be used in character development. This study aims to explore the content of character education values in Indramayu folklore and its utilization as a media for character education. The researcher utilizes the theory of character education initiated by Lickona. The method used in this research is qualitative method with content analysis approach. Data in the form of folktales contained in two books of folklore collection by Kusyoto and Supali Kasim were collected using the flowing document analysis technique. The results of this study indicate that Indramayu folktales contain character education values including moral knowledge, moral feelings, and moral action. Moral knowledge includes moral awareness, wise decision making, knowing moral values, and being able to take perspective. Moral feelings include loving kindness and having a conscience. Moral actions include having the competence and will to solve moral problems. The findings of this study can be utilized as a medium for instilling the value of character education for students, especially in schools located in the Indramayu Regency area.